Parents ethanol use impairs ethanol-naive offspring development and reproduction - Fioravante, Vanessa Caroline [UNESP]; Godoi, Alana Rezende [UNESP]; De Barros Camargo, Victória Mokarzel [UNESP]; Do Nascimento, Renata Steffany [UNESP]; Felipe Pinheiro, Patricia Fernanda [UNESP]; Martinez, Francisco Eduardo [UNESP] (Oxford University Press (OUP), 2021)
Parental ethanol consumption can influence the offspring phenotype. In this way, we analyzed the impairments of maternal and paternal high ethanol consumption during postpuberty on the physical development, feeding pattern, puberty onset and reproductive function of ethanol-naive offspring to birth to adulthood. Female and male UChB rats (voluntary 10%, v/v ethanol consumer) were divided into a control group (C) and an ethanol exposed group (E) from 65 to 80 days of age. The C and E were mated at 100 days. The maternal parameters and offspring development and reproduction parameters were monitored. We observed reduced feeding intake and body weight in the dams of E group throughout gestation and lactation period. Delay in physical development, lower body weight and altered feeding pattern were observed in female and male offspring of E group. In addition, the puberty onset was delayed in both sexes, with lower testosterone levels in the juvenile and pubertal males. There was a prolongation on the estrous and proestrus phases in females from E but the estrous cycle duration did not change between groups. Ovary and uterus weight were reduced in pubertal and adult females from E group. Reduced epididymis and seminal vesicle weight, increased sperm abnormalities, decrease in the daily sperm production and accelerated epididymal transit time were observed in E males. The high maternal and paternal ethanol use on postpuberty impairs the parameters of ethanol-naive offspring inducing alteration on development and reproduction.